X-ray powder diffraction data for menthyl lactate, C13H24O3. Issue 4 (1st August 2016) - Liao, Xiaoxiang; Tang, Jianguo; Yuan, Dalin; Huang, Yanmei; Yang, Hongqin; Zhao, Wei; Yang, Ji; Fan, Ying; Li, Hui
Abstract : X-ray powder diffraction data, unit-cell parameters, and space group for menthyl lactate, C13 H24 O3, are reported [ a = 5.522(6) Å, b = 11.795(8) Å, c = 17.780(6) Å, α = 50.632(3)°, β = 90.000(0)°, γ = 117.632(4)°, unit-cell volume V = 716.392(0) Å 3, Z = 2, and space group P −1]. All measured lines were indexed and no detectable impurities were observed.